On the Issue of the Concepts Ratio "Criminal Prosecution", "Charge", "Suspicion", "Preliminary Investigation" - E. I. Zemlyanitsin (Сибирское юридическое обозрение, 2013)
An attempt is made to correlate such legal categories as "criminal prosecution", "charge", "suspicion", "preliminary investigation". Here is presented the comparative analysis of charge and suspicion as inherent elements of the agencies activities exercising criminal prosecution.